Title Vads Collection: Constance Howard Resource and Research Centre in Textiles: Material Collection - Object Name: storage bag front
Brief Physical Description: Two rectangular, layered cloths quilted together with open, geometric patterns formed by arrangements of running stitch and organised into stripes. Select this link for more description information.